ISOLASI ZAT WARNA BARU Monascus purpureus DARI HASIL FERMENTASI PADAT DENGAN BERAS SEBAGAI SUBSTRAT - Yuliana, Anna (Journal of Pharmacopolium, 2018)
Monascus purpureus is a mold capable of producing pigment as secondary metabolites. Pigments of Monascus purpureus isolated from rice fermented solid known as red yeast rice. This study was conducted toMonascus purpureus know the potential in generating new compounds of pigment produced by solid fermentation process with rice as a substrate. The results indicate insulation compounds and new compounds of pigment Monascus purpureus. Beginning with an analysis of Thin Layer Chromatography (TLC) using the mobile phase n-hexane and ethyl acetate (7:3) with a Rf value obtained was 0.71. Analysis with UV-Vis spectrophotometry against red yeast rice extract aims to determine the maximum wavelength. The results of the analysis of UV-Vis spectrophotometry obtained one peak an absorption at 0.255 with a wavelength of 486 nm which showed that the red pigment monascorubramin compounds in Monascus purpureus. Isolation of Monascus purpureus pigments by Preparative Thin Layer Chromatography (Preparative TLC) using the mobile phase n-hexane and ethyl acetate (7:3). Results isolation pigment Monascus purpureus form of a ribbon that can fluoresces atÎ» 365 nm UV light with a Rf value obtained was 0.73 were further identification of the molecular weights of compounds Monascus purpureus using HPLC instruments with detectors MS (Mass Spectrometer). The results of LC-MS analysis of a sample INACC-F01 showed a new compound which has a molecular weight of 357.41 and based on the literature that the same compounds with molecular weight is Monascopyridine C which is a derived compound from Monascus red pigment that is monascorubramin and rubropunctamin.Â Keywords:Monascus purpureus, pigment, angkak, Preparative TLC, LC-MS.